2015
DOI: 10.1128/jvi.01028-15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Activity Aggravates Coxsackievirus B3-Induced Myocarditis by Promoting Viral Replication and Myocardial Apoptosis

Abstract: Viral myocarditis, which is most prevalently caused by coxsackievirus B3 (CVB3), is a serious clinical condition characterized by excessive myocardial inflammation. Recent studies suggest that regulation of protein acetylation levels by inhibiting histone deacetylase (HDAC) activity modulates inflammatory response and shows promise as a therapy for several inflammatory diseases. However, the role of HDAC activity in viral myocarditis is still not fully understood. Here, we aim to investigate the role of HDAC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Classically HDACs deacetylate nucleosome histones and alter the electrostatic properties of chromatin in a manner that represses gene expression (30, 31). Inhibition of HDACs using small molecules such as butyrate, VPA or trichostatin A exerts multiple cardioprotective effects, such as the anti-hypertrophy (32, 33), anti-fibrosis (34, 35), anti-oxidative stress (36), anti-inflammation (37, 38), and anti-apoptosis (39) under non-diabetic conditions, and also anti-DCM (14, 15). Although HDACs are the promising therapeutic target for multiple cardiovascular diseases, the diversity of HDAC isoforms constrain the practice.…”
Section: Discussionmentioning
confidence: 99%
“…Classically HDACs deacetylate nucleosome histones and alter the electrostatic properties of chromatin in a manner that represses gene expression (30, 31). Inhibition of HDACs using small molecules such as butyrate, VPA or trichostatin A exerts multiple cardioprotective effects, such as the anti-hypertrophy (32, 33), anti-fibrosis (34, 35), anti-oxidative stress (36), anti-inflammation (37, 38), and anti-apoptosis (39) under non-diabetic conditions, and also anti-DCM (14, 15). Although HDACs are the promising therapeutic target for multiple cardiovascular diseases, the diversity of HDAC isoforms constrain the practice.…”
Section: Discussionmentioning
confidence: 99%
“…[32] This finding is also supported by wortmannin inhibition of coxsackievirus replication in infected mice treated with a histone-deacetylase which induced replication by inhibiting autophagy and inducing apoptosis. [33] Geldanamycin is a benzoquinone with known antimalrial activity. It belongs to a group of drugs called ansamycins.…”
Section: ]mentioning
confidence: 99%
“…Accumulating evidence indicates that autophagy is involved in various pathological processes, including cancer and metabolic and neurodegenerative disorders (23,24). Recent studies have shown that autophagy is an important host factor in the regulation of the replication of diverse viruses, such as dengue virus, poliovirus, influenza virus A, and coxsackievirus B3 virus, as well as HBV (25)(26)(27)(28)(29)(30)(31)(32). Evidence indicates that HBV can activate autophagosome formation, which is required for its own replication (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%